Five open questions about prediction markets - Justin Wolfers; Eric Zitzewitz (Institute for the Study of Labor (IZA), 2006)
Interest in prediction markets has increased in the last decade, driven in part by the hope that these markets will prove to be valuable tools in forecasting, decision-making and risk management - in both the public and private sectors. This paper outlines five open questions in the literature, and we argue that resolving these questions is crucial to determining whether current optimism about prediction markets will be realized.
Keywords: C9; D7; D8; G1; M2; 330; prediction markets; information markets; event futures; political forecasting; prediction IVs; Prognoseverfahren; Informationsdienstleistung; Manipulation; Risikomanagement; Wirtschaftsprognose; Börsenspiel